2021
DOI: 10.3389/fphar.2021.698375
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anticancer Properties of Geranyl Isovalerate, an Active Ingredient of Argyreia nervosa Extract in Colorectal Cancer Cells

Abstract: Chemotherapy is a general treatment procedure for cancer. The diversity in cancer incidence and the failure of therapy due to chemoresistance lead to increased cancer-related deaths. Therefore, new drugs with fewer secondary complications targeting diverse pathways are the need of the hour. Geranyl isovalerate (GIV), one of the active ingredients of ethyl acetate fraction of Argyreia nervosa is routinely used as a food flavoring agent. In this study, we found that GIV also exhibits anticancer activity when tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The initial documentation of geranyl isovalerate occurred in a medical journal publication in September of 2021, where its biological properties were elucidated. Upon ingestion by the human body, this compound can directly interact with the epithelial cells of the gastrointestinal tract and exhibit anti-cancer properties [43]. The additional experiments showed that perceptual interactions among the key aroma compounds in Merlot wine vary with different geranyl isovalerate concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…The initial documentation of geranyl isovalerate occurred in a medical journal publication in September of 2021, where its biological properties were elucidated. Upon ingestion by the human body, this compound can directly interact with the epithelial cells of the gastrointestinal tract and exhibit anti-cancer properties [43]. The additional experiments showed that perceptual interactions among the key aroma compounds in Merlot wine vary with different geranyl isovalerate concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Geranyl isovalerate (GIV) found in landraces BG-70 and NSRP (Supplementary Data 2) is among the least investigated ethnopharmacological compounds commercially utilized as a food flavouring agent and a constituent of essential oils ( Iftikhar, Ahmed, & Qamar, 2019 ; Kumar, Sharma, Thukral, & Bhardwaj, 2015 ). GIV also possesses antitumor, antihyperglycemic, immunomodulatory, anti-inflammatory, and analgesic properties, thus making it an ideal food supplement and an alternative chemotherapeutic ( Rasool, Sharma, Anand, Magani, & Tantravahi, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress-mediated cell death was supported by increased ROS (reactive oxygen species) production, MMP (matrix metalloproteinase) loss, decreased antiapoptotic gene expression, and enhanced proapoptotic gene expression (36). Menthol found in Gomutra used as a topical antipruritic and in cough drops and inhalers (37). Some new compounds were also observed in Gomutrasava that were absent in Gomutra.…”
Section: Discussionmentioning
confidence: 99%